2018
DOI: 10.3390/machines6030040
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Stainless Steel SAE304 Laser Engraving Cutting Conditions

Abstract: Laser machining processes are a new entrant and a rapidly evolving type of non-conventional machining process which allows the machining of complex geometries with high precision, surface quality and productivity in a wide range of materials. Thus, the need for creating a method has emerged that will help the laser machine operator to select the optimal process parameters. In this study an experimental investigation of the effect of the process parameters on the effectiveness of the laser engraving process was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Hence, this result might be due to the combined effect of multiple concurrent parameters used to determine the laser marking of adequate quality at lower processing times and reduced CO 2 emission. However, from Figure 3d, it is evident that laser power and scanning speed have the most significant positive and negative impacts on MRR, as similarly evidenced in the laser engraving of metals [49]. As stated previously, the results confirmed that all the process variables contributed in the definition of the surface roughness so that, as also observed in [50], the concurrent effects are difficult to be discerned.…”
Section: Comparative Parametric Effects On Response Variablessupporting
confidence: 75%
“…Hence, this result might be due to the combined effect of multiple concurrent parameters used to determine the laser marking of adequate quality at lower processing times and reduced CO 2 emission. However, from Figure 3d, it is evident that laser power and scanning speed have the most significant positive and negative impacts on MRR, as similarly evidenced in the laser engraving of metals [49]. As stated previously, the results confirmed that all the process variables contributed in the definition of the surface roughness so that, as also observed in [50], the concurrent effects are difficult to be discerned.…”
Section: Comparative Parametric Effects On Response Variablessupporting
confidence: 75%
“…This makes it necessary to account for these differences when designing the process. Previous research [12][13][14][15][16][17] has provided a summary of the factors that might impact the surface roughness. These factors include scanning speed, focal distance, scan gap, and laser power.…”
Section: The Effect Of Co2 Laser Engrave Parameters On Surface Roughn...mentioning
confidence: 99%
“…The power of the fibre resonator in this type of laser ranges from 0.5 kW to 8 kW, and cutting speeds exceed 20 m/min. Therefore, it is possible to perform cutting speed optimisation [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%